2017
DOI: 10.1038/ni.3683
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of IRF1 and BATF in forming chromatin landscape during type 1 regulatory cell differentiation

Abstract: Type 1 regulatory T (Tr1) cells are induced by interleukin-27 (IL-27) and have critical roles in the control of autoimmunity and resolution of inflammation. Here, we show that the transcription factors IRF1 and BATF are induced early during treatment with IL-27 and are required for the differentiation and function of Tr1 cells in vitro and in vivo. Epigenetic and transcriptional analyses reveal that both transcription factors influence chromatin accessibility and expression of genes required for Tr1 cell funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 47 publications
6
110
0
Order By: Relevance
“…69 The motif for TEAD transcription factors is over-represented in PGR binding intervals across all four specimens (Table S12) and expression of TEAD1, TEAD2, TEAD3, and TEAD4 is detected in both NP and TP myometrial tissues (Table S2). The BATF family transcription factors function as a pioneer factor that controls chromatin accessibility 70 and serve as co-regulators for PGR, NR3C1, and AP-1. [71][72][73] The binding motif for BATF, members of the AP-1 superfamily, is among the top enriched motifs within PGR binding regions in all four myometrial samples (Table S12) and BATF, BATF2, and BATF3 are all expressed in both stages of the examined myometrium (Table S2).…”
Section: Pgr Genome Occupancy In the Myometrial Tissuesmentioning
confidence: 99%
“…69 The motif for TEAD transcription factors is over-represented in PGR binding intervals across all four specimens (Table S12) and expression of TEAD1, TEAD2, TEAD3, and TEAD4 is detected in both NP and TP myometrial tissues (Table S2). The BATF family transcription factors function as a pioneer factor that controls chromatin accessibility 70 and serve as co-regulators for PGR, NR3C1, and AP-1. [71][72][73] The binding motif for BATF, members of the AP-1 superfamily, is among the top enriched motifs within PGR binding regions in all four myometrial samples (Table S12) and BATF, BATF2, and BATF3 are all expressed in both stages of the examined myometrium (Table S2).…”
Section: Pgr Genome Occupancy In the Myometrial Tissuesmentioning
confidence: 99%
“…We further found that some of the GR binding peaks in the Havcr2, Lag3, and IL10 loci overlapped regions of accessible chromatin (based on ATAC-seq) in IL-27-stimulated T cells (Karwacz et al, 2017), which are known to express high levels of these molecules (Chihara et al, 2018) (Figure S6). We therefore tested the effect of GR binding to the cis-regulatory elements in these peaks in the Havcr2, Pdcd1, Lag3, and Tigit loci using luciferase reporter assays.…”
Section: The Glucocorticoid Receptor Transactivates the Expression Ofmentioning
confidence: 89%
“…We therefore tested the effect of GR binding to the cis-regulatory elements in these peaks in the Havcr2, Pdcd1, Lag3, and Tigit loci using luciferase reporter assays. For IL10, we utilized luciferase reporters of a previously established enhancer element of Il10 -HSS + 2.98 as well as the proximal promoter (-1.5kb) (Karwacz et al, 2017). We transfected the different luciferase reporter constructs along with a Nr3c1 expressing vector or empty vector into 293T cells and treated the cells with glucocorticoid to assay the transactivation capability of the GR.…”
Section: The Glucocorticoid Receptor Transactivates the Expression Ofmentioning
confidence: 99%
“…Recently, the transcription factors IRF1 and BATF have also been shown to be required for Tr1 cell differentiation. 41 In this review, we discuss the contribution of bacterial and dietary components such as short-chain fatty acids (SCFAs), vitamin A-derived retinoic acid (RA) and dietary antigens to the development, functional maturation and maintenance of intestinal Foxp3 + Treg cells that are crucial for providing tolerogenic microenvironment in the gut.…”
Section: Regulatory T Cells (Treg Cells) Have a Central Role In The Mmentioning
confidence: 99%
“…IL‐21 secreted by Tr1 cells acts in an autocrine manner to stabilize the Tr1 cell phenotype. Recently, the transcription factors IRF1 and BATF have also been shown to be required for Tr1 cell differentiation 41 …”
mentioning
confidence: 99%